Ecosystem-based Management through the lenses of International Seabed Authority stakeholders: current status, implications, and opportunities for the deep-sea mining regime in the Area - Guilhon, Maila; Xavier, Luciana Yokoyama; von Pogrell, Luise; Singh, Pradeep; Christiansen, Sabine; Turra, Alexander (Frontiers in Marine Science, 2023)
The ocean is threatened by human activities, which undermine the health of its ecosystems. To overcome this scenario, there is a converging understanding that a more encompassing approach, such as Ecosystem-based Management (EBM), is essential to manage human activities. EBM implementation in scenarios of limited knowledge and potentially irreversible impacts, such as deep-sea mining (DSM), is thus highly appropriate, although the translation of this approach into practice is not intuitive and rather challenging. The International Seabed Authority (ISA), the organization with the mandate to award exploration and exploitation contracts for minerals on the international seabed, has recognized the need to incorporate EBM in its instruments but has not specified how to implement it. Through an online survey and in-depth interviews, ISA stakeholders have been inquired about their perception of the understanding, current status, implications, and opportunities of EBM for the deep-sea mining regime. The findings reveal that stakeholders perceive EBM as more related to ecological and impact aspects and less with participation, socio-ecological systems interlinks, and other forms of knowledge that are not scientific. Few respondents recognize EBM within the ISA, reporting its reflection in management instruments such as Regional Environmental Management Plans and Environmental Impact Assessments. No common definition exists, regarded as an obstacle to decision-making and EBM operationalization. According to them, opportunities to improve EBM implementation include collaboration with organizations already familiar with EBM, capacity development activities, workshops, and dedicated side events focusing on the issue. Finally, most of them recognize that a lack of consensus regarding EBM can impact decision-making and EBM operationalization, thus compromising ISA’s mandate. In this context, the clarification on what EBM entails for the seabed mining regime should be a matter of major interest to the ISA and all its stakeholders, as the mineral resources found in the seabed beyond the limits of national jurisdictions (the Area) are the common heritage of humankind, and therefore, its maintenance and benefits must be ensured to future generations.